OSL-SAR dating of sediments from Brazilian aeolian system: Dama Branca, Rio de Janeiro, morphodynamic study - Lucas Sátiro do Carmo (Brazilian Journal of Radiation Sciences)
It has been reported that the formation and stabilization of coastal dune fields in Brazil have a dependence on the climatic changes, Relative Sea Level (RSL) variations, etc. In this work, a dune field known as “Dama Branca”, located in the town of Cabo Frio, Rio de Janeiro, has been studied to understand its mobility, formation and stabilization. Dating by trapped charge dating techniques as Optically Stimulated Luminescence (OSL) using the Single Aliquot Regenerative protocol (SAR), helps us to understand the formation and dynamics of aeolian systems in Brazil. Samples from two positions; DB and 2DB, were collected from different heights and points for dating. The results obtained by OSL-SAR showed that ages decrease as the height from the dune base increase and older samples are found in deeper horizontal positions. The ages from the base of the studied dunes indicated that its stabilization occurred during the recess of the sea level and that erosion caused by the wind action is revealing an old generation of this dune filed.